2022
DOI: 10.1007/s00167-022-07110-3
|View full text |Cite
|
Sign up to set email alerts
|

Poorer functional Outcomes in Patients with Multi-Ligamentous Knee Injury with Concomitant Patellar Tendon Ruptures at 5 years Follow-Up

Abstract: PurposeMulti‐ligamentous knee injuries (MLKIs) are high‐energy injuries that may infrequently present with concomitant patellar tendon rupture. There is limited information in the literature regarding these rare presentations, with even less information regarding clinical outcomes. Using propensity‐score matching, the purpose of this study was to compare the outcomes of MLKIs with and without patellar tendon ruptures and to investigate the overall predictors of these outcomes. MethodsTwelve patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Similarly, a recent Delphi panel suggested the inclusion of an additional “-O” modifier to indicate open injuries 26 . Adding EM injuries as a “sixth stratified level” has been previously suggested by Mojica et al 7 . The widely used Schenck KD Classification captures a heterogeneous group of injuries, and adding such a modifier can improve our ability to communicate and guide treatment for concurrent EM injury.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, a recent Delphi panel suggested the inclusion of an additional “-O” modifier to indicate open injuries 26 . Adding EM injuries as a “sixth stratified level” has been previously suggested by Mojica et al 7 . The widely used Schenck KD Classification captures a heterogeneous group of injuries, and adding such a modifier can improve our ability to communicate and guide treatment for concurrent EM injury.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative joint mobilization is important to reduce the development of arthrofibrosis and knee stiffness, but it must be balanced against protection of the EM repair 9 . Mojica et al reported that patients in their cohort were treated with a hinged knee brace locked in extension for a minimum of 3 weeks; however, the period of immobilization was dependent on the surgeon and was often based on the number of ligaments reconstructed 7 . Additionally, 75% of the patients in that study underwent staged treatment of the concomitant EM injury and MLKI 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations